2018
DOI: 10.1016/j.stemcr.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling Accelerates Senescence of Human Bone-Derived CD271 and SSEA-4 Double-Positive Mesenchymal Stromal Cells

Abstract: SummaryIt is generally thought that the proliferative capacity and differentiation potential of somatic stem cells, including mesenchymal stromal/stem cells (MSCs) and hematopoietic stem cells, decline with age. We investigated the effects of aging on human bone-derived MSCs expressing CD271 and SSEA-4 (double-positive MSCs [DPMSCs]). The percentages of DPMSCs in bone tissue decreased significantly with age. The DPMSCs from elderly patients (old DPMSCs) showed cellular senescence, which was evidenced by low gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…However, it was reported that induction of cell senescence in stromal cells by genotoxic agents may impair bone differentiation in a p53‐dependent manner, thus supporting the concept that in physiologically aged MSC, the establishment of a presenescence state could contribute to slightly impair the induction of osteogenic genes upon differentiation cues (Despars, Carbonneau, Bardeau, Coutu, & Beausejour, ). Although donor variability may mask any differentiation skewing between young and aged MSC, data in the literature reporting on an unbalanced differentiation of aged MSCs may instead reflect a different MSC source (adipose tissues derived vs. BM‐derived) (Wegmeyer et al, ), different culture conditions (FBS vs. platelet lysate enriched culture medium), or the underlying pathologies of elderly subjects (Kawamura et al, ). Indeed, most data available to date on human aging of the stromal compartment are generated on MSC obtained during surgical procedures for treatment of different age‐related pathologies with strong immunological alterations and do not represent the biology of stromal bone marrow cells during physiological aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported that induction of cell senescence in stromal cells by genotoxic agents may impair bone differentiation in a p53‐dependent manner, thus supporting the concept that in physiologically aged MSC, the establishment of a presenescence state could contribute to slightly impair the induction of osteogenic genes upon differentiation cues (Despars, Carbonneau, Bardeau, Coutu, & Beausejour, ). Although donor variability may mask any differentiation skewing between young and aged MSC, data in the literature reporting on an unbalanced differentiation of aged MSCs may instead reflect a different MSC source (adipose tissues derived vs. BM‐derived) (Wegmeyer et al, ), different culture conditions (FBS vs. platelet lysate enriched culture medium), or the underlying pathologies of elderly subjects (Kawamura et al, ). Indeed, most data available to date on human aging of the stromal compartment are generated on MSC obtained during surgical procedures for treatment of different age‐related pathologies with strong immunological alterations and do not represent the biology of stromal bone marrow cells during physiological aging.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that, in concert with a cell‐autonomous dysfunction of aged MSC, extrinsic factors may as well alter MSC crosstalks with other BM cellular components. TGF‐β pathway has only recently emerged as a key mediator of the senescence associated with aged MSC derived from osteoarthritic bones (Kawamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, Repsox was used to replace Sox2 for pluripotency improvement, instead of directly increasing the expression of Sox2. We showed that the expressions of Oct4, Sox2, and TGF-β strongly suppressed the osteogenic differentiation of human BMSC, while its antagonist 1D11 tended to enhance the osteogenic differentiation of these cells (Kawamura et al, 2018). In vivo experiments also revealed that administration of TGF-β antagonist 1D11 enhanced the osteogenesis in mouse (Edwards et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Repsox could upregulate Bax and Bcl2 in the reprogrammed embryos, and improve the proliferative capacity of neural progenitors derived from human MSC (Aguilera‐Castrejon et al, ; Zhu et al, ). It is reported that TGF‐β induced apoptosis and senescence of mouse BMSC (Wu et al, ; Zhang, Ren, & Wu, ), and suppressed the proliferation of human BMSC (Kawamura et al, ). Consistently, we observed that TGFβR‐1/ALK5 inhibitor Repsox enhanced the expression of the proliferation gene and improved the antiapoptosis capacity of bBMSC by inhibiting TGF‐β signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation